BULL'S EYE: IS THIS PHENOMENON GIVEN ENOUGH ATTENTION? - Gjeorgjieva Janev, Olivera; Lushi Selimi, Mediha; Pecanova Dungevska, Blagica; Pachoska, Vesna; Karanfilovski, Vlatko; Pandilov, Stefan; Damjanovska Krstikj, Ljubinka (Journal of Morphological Sciences; Vol 7 No 3 (2024): JMS, 2024)
Chloroquine maculopathy is  not such a  rare complication of long-term use of chloroquine preparations in the treatment of rheumatological diseases. Its early detection is of exceptional importance for timely discontinuation of the drug in order to prevent irreversible vision damage. The aim of this Article is  to present a case of a 62-year-old patient with bull's eye maculopathy as a result of long-term use of chloroquine due to systemic lupus erythematosus. The patient appeared with  blurring and distortion of the pericentral vision. She was ophthalmologically evaluated with fundoscopic examination, autofluorescence, perimetry, optical coherent tomography which together with her  medical history established a diagnosis of chloroquine maculopathy. Chloroquine therapy was discontinued and the patient is regularly monitored  by a Rheumatologist and an Ophthalmologist, with no disease progression so far. Keywords: Bull’s eye, retinopathy, hydroxychloroquine